2014
DOI: 10.1111/ics.12136
|View full text |Cite
|
Sign up to set email alerts
|

Effects of water activity and low molecular weight humectants on skin permeability and hydration dynamics – a double‐blind, randomized and controlled study

Abstract: Synopsis Objectives The mammalian skin is a barrier that effectively separates the water‐rich interior of the body from the normally dryer exterior. Changes in the external conditions, for example ambient humidity, have been shown to affect the skin barrier properties. The prime objective of this study was to evaluate the effect of water activity of a topical formulation on skin hydration and permeability. A second objective was to gain more understanding on how two commonly used humectants, urea and glycerol,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 22 publications
(43 reference statements)
1
13
0
Order By: Relevance
“…Even though the moisturizing property of glyceryl ether is lower than glycerol, it still exhibits a good moisturizing effect to skin. A high skin hydration level of emulsion containing glycerol was reported by Alber et al (2014). The superior moisturizing property of glycerol could be attributed to the three hydroxyl groups in the glycerol molecule, whereas the glyceryl ether has only two hydroxyl groups.…”
Section: Resultsmentioning
confidence: 94%
“…Even though the moisturizing property of glyceryl ether is lower than glycerol, it still exhibits a good moisturizing effect to skin. A high skin hydration level of emulsion containing glycerol was reported by Alber et al (2014). The superior moisturizing property of glycerol could be attributed to the three hydroxyl groups in the glycerol molecule, whereas the glyceryl ether has only two hydroxyl groups.…”
Section: Resultsmentioning
confidence: 94%
“…The observed interphasic localization of the RNA in the emulsion suggests a surfactant effect, presumably effect of multiple interactions with the functional groups of the components in the emulsion (Figure ) . Mechanisms for urea‐dependent skin permeability enhancement were previously discussed; for example, in the works Albèr et al and Björklund et al described the enhancement of skin permeability mediated by urea, as effect of ultrastructural changes . Furthermore, Jatana et al suggested that commonly used active ingredients, such as urea and glycerol, could highly affect the skin penetration of particulates, and thus, it could possibly results in the cutaneous deposition of water‐soluble macromolecules up to a size of few nanometres .…”
Section: Discussionmentioning
confidence: 96%
“…Several studies have demonstrated that glycerine promotes skin hydration and can also increase skin permeability [45][46][47][48].…”
Section: Discussionmentioning
confidence: 99%